PEMBERDAYAAN AKSARA MASYARAKAT PEDESAAN : EVALUASI PROGRAM KEAKSARAAN FUNGSIONAL PADA KELOMPOK “NGUDI KAWRUH” DI KELURAHAN PASAR KLIWON KOTA SURAKARTA - Riza Wulandari (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2017)
The problem of illiteracy is still a concern of the Government of the city of Surakarta majority experienced by communities with medium economies down. Surakarta has the Functional Literacy Programme for the illiterate. This is already underway so that necessary related Evaluation of the program. This study is a qualitative study aiming to find out the success of the functional Literacy Program in the group